Poly-β-hydroxybutyrate (PHB) Depolymerase from Fusarium solani Thom. (16th August 2012) - Shivakumar, Srividya
Abstract : Fusarium solani Thom produced maximum PHB depolymerase by 48 h when grown in BHM containing 0.2%, w/v PHB, pH 8.0 at 25 ° C . Statistical optimization studies using Plackett Burman design of PHB depolymerase production yielded maximum PHB depolymerase activity after 2 days as against 4 days in the unoptimized conditions with a 2-fold increase in activity. Partial purification of the extracellular poly- β -hydroxybutyrate (PHB) depolymerase PHAZ Fus from F. solani Thom by two steps using ammonium sulphate (80% saturation) and affinity chromatography using concanavalin-A yielded 162.3-fold purity and 63% recovery of protein. The enzyme composed of a single polypeptide chain of 85 KDa, as determined by SDS-PAGE. The enzyme stained positive for glycoprotein by PAS staining. Optimum enzyme activity was detected at pH 7.0 and 55 ° C . The enzyme was stable at pH 7.0 and 55°C for 24 h with a residual activity of almost 85%. Paper chromatography revealed β -hydroxybutyrate monomer as the major end product of PHB hydrolysis. Complete inhibition of the enzyme by 1 mM HgCl2 (100%) indicated the importance of essential disulfide bonds (cystine residues) for enzyme activity or probably for maintaining the native enzyme structure.